Efficacy and Safety of Switching to Dolutegravir With Boosted Darunavir in Virologically Suppressed Adults With HIV-1: A Randomized, Open-Label, Multicenter, Phase 3, Noninferiority Trial: The DUALIS Study. (13th August 2020) - Spinner, Christoph D; Kümmerle, Tim; Schneider, Jochen; Cordes, Christiane; Heiken, Hans; Stellbrink, Hans-Jürgen; Krznaric, Ivanka; Scholten, Stephan; Jensen, Björn; Wyen, Christoph; Viehweger, Marin; Lehmann, Clara; et al.
Abstract: Background: Dolutegravir (DTG) and boosted darunavir (bDRV) are potent antiretrovirals with a high resistance barrier and might be valuable switch options for people with HIV (PWH). Methods: DUALIS, a randomized, open-label, phase 3b, noninferiority clinical trial, compared the switch to DTG + bDRV (2DR) with continuation of 2 nucleoside reverse transcriptase inhibitors (2NRTI) + bDRV (3DR). PWH with HIV RNA <50 copies/mL taking 2NRTI + bDRV (3DR) for ≥24 weeks (1 accepted blip <200 copies/mL) were randomized to either switch to DTG 50 mg + DRV 800 mg (boosted with 100 mg of ritonavir) or continue taking 3DR. The primary end point (PE) was the proportion of HIV RNA <50 copies/mL at week (W) 48. Change in NRTI backbone was not classified as failure. The estimated sample size for PE analysis was 292; the noninferiority margin was ≤–10.0%. Results: In total, 263 subjects were randomized and treated (2DR n = 131, 3DR n = 132; 90.1% male; 89.7% Caucasian; median age [interquartile range], 48 [39–54] years). At W48, 86.3% (n = 113/131) of the 2DR subject and 87.9% (n = 116/132) of the 3DR subjects had HIV RNA <50 copies/mL; the difference between arms was –1.6% (95.48% CI, based on the adjusted alpha level accounting for the interim analysis at W24, –9.9% to +6.7%; discontinuations due to adverse events: 2DR, 4.6% [n = 6]; 3DR, 0.8% [n = 1]). Kaplan-Meier estimates of confirmed HIV RNA ≥50 copies/mL at W48 were 1.6% (n = 2) in the 2DR and 3.1% (n = 4) in the 3DR group. Development of treatment-emergent resistance was not observed. Conclusions: Switching to DTG + bDRV was noninferior to continuing 3DR in subjects already treated with bDRV. Abstract : The DUALIS phase-III study demonstrated non-inferiority of an effective and safe switch to dolutegravir combined with boosted darunavir (2DR) in suppressed people living with HIV as compared to continue 2 nucleoside reverse transcriptase inhibitors in combination with boosted darunavir (3DR).